2007
DOI: 10.2478/s11756-007-0127-z
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme variations in six natural populations of scots pine (Pinus sylvestris) in Turkey

Abstract: Genetic variation in six natural populations of Scots pine (Pinus sylvestris L.) was determined with isoenzyme analyses. For this purpose, haploid female gametophytes of seeds and horizontal starch gel electrophoresis technique were used. A total of 17 loci and 58 alleles were observed in studying 10 enzyme systems. The average proportion of polymorphic loci for populations ranged from 58.8% to 70.6%. The average number of alleles per locus per population was 2.65. The mean estimated expected heterozygosity (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 14 publications
4
13
1
Order By: Relevance
“…3, 5), which have not been biometrically documented till now. The pattern of morphological differentiation in the Anatolian populations of P. sylvestris is similar to those already described using isozyme variation (Bilgen and Kaya 2007). The isolation of the eastern from western Anatolian populations of P. sylvestris can be explained by the mountain ranges known as the ''Anatolian diagonal''.…”
Section: Differentiation Within Regionssupporting
confidence: 82%
See 2 more Smart Citations
“…3, 5), which have not been biometrically documented till now. The pattern of morphological differentiation in the Anatolian populations of P. sylvestris is similar to those already described using isozyme variation (Bilgen and Kaya 2007). The isolation of the eastern from western Anatolian populations of P. sylvestris can be explained by the mountain ranges known as the ''Anatolian diagonal''.…”
Section: Differentiation Within Regionssupporting
confidence: 82%
“…Pyhäjärvi et al (2007) have lately shown significant differences between Turkish and Spanish Scots pine populations in both nuclear and mitochondrial DNA. Conversely, a low level of genetic differentiation (F ST = 0.014) among several populations from Turkey was shown on the basis of isoenzymes (Turna 2003;Bilgen and Kaya 2007). The degree of population differentiation in Bulgaria revealed by cpDNA was not very high (F ST = 0.048) (Naydenov et al 2005).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our hypothesis is that natural populations in the refugial areas, in addition to possessing imprints of historical events, are also distinctive due to adaptations to different habitat extremes on the periphery. This hypothesis is supported by studies performed on populations from Central and Northern Europe, the Balkans, Iberia, and Anatolia (Staszkiewicz, 1961;Tobolski & Hanover, 1971;Mejnartowicz, 1979;Prus-Glowacki & Stephan, 1994;Alía et al, 2001;Prus-Głowacki et al, 2003;Turna, 2003;Labra et al, 2006;Bilgen & Kaya, 2007;Pyhäjärvi et al, 2007;Semiz et al, 2007;Dzialuk et al, 2009;Jasińska et al, 2014). Based on these works, it can be concluded that populations in refugial areas display not only 'geographic marks', but also genetic differences and differentiation at the phenotypic level.…”
Section: Introductionsupporting
confidence: 64%
“…al., 2010;Şevik, 2010), isosymes analysis (Bilgen and Kaya, 2007;Turna, 2003) and DNA markers (Clark et. al., 2000;Goldstein, 1995 Shea (1990) reported that the variation among the populations is small (1,3%) but significant in Abies Lasiocarpa.…”
Section: Discussionmentioning
confidence: 99%